Recent Advances in Understanding the Role of Growth Regulators in Plant Growth and Development in Vitro-I. Conventional Growth Regulators - Kumar, Suresh; Singh, Rohtas; Kalia, Sanjay; Sharma, S. K.; Kalia, Andrajwant K. (Indian Forester, 2016)
Growth regulators, a diverse array of organic compounds, are critical components in determining developmental pathways in plants. They interact at the cellular level to produce physiological and morphological effects. Our understanding about transport, metabolism and mode of action of growth regulators in plants has considerably increased in the recent years. Discovery of the chemicals that interfere with synthesis, transport and action of endogenous growth regulators have further improved our knowledge regarding the role of plant growth regulators (PGRs) in plant’s growth and development. A number of PGRs are being used in plant cell, tissue and organ cultures for decades, while many of them have recently been discovered and tested for their effects in vitro. In this review, we attempted to summarize the remarkable progress that has been made over the past decades towards understanding PGRs. The progress is further improving our knowledge of the molecular mechanisms of their action, and beginning to explain how PGRs not only have direct influence on cellular growth, but also control various aspects of plant’s growth in vivo as well as in vitro.